Você está na página 1de 10

V

W

F

F (V, W ) V W

F (V ) = F (V, V )

GL(V ) = {f F (V ) : f }

n N M n (F) n F

n N GL(n, F) = {A M n (F) : A }

G V F G V ρ : G GL(V )

ρ : G GL(V ) G V g, h G

ρ(gh) = ρ(g) ρ(h),

ρ(e) = V ,

ρ g 1 = (ρ(g))

e G

ρ : G GL(V ) G V ρ V (ρ) ρ

G V F ρ : G

, e n }

V g G ρ(g) E

GL(V ) G V E = {e 1 ,

A(g)

R : G GL(n, F)

g

A(g)

G R : G GL(n, F)

G

G F

G V n

ρ : G GL(V )

g

V

G G n

R : G GL(n, F)

g

I n .

n N F

ρ : S n GL(F n )

ρ(σ)(v 1 ,

σ

ρ(σ)

, v n ) = (v σ 1 (1) ,

,

v σ 1 (n) ),

, v n ) F n S n

GL(F) F × F λ F ×

(v 1 ,

f λ : F F

x

λx

1 G G F ×

n N F

: S n F ×

σ

(σ)

S n (σ) σ

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2 F ρ 1 ρ 2 f : V 1 V 2 g G

f ρ 1 (g) = ρ 2 (g) f.

f ρ 1 ρ 2

σ 1 σ 1 σ

G ρ : G GL(V ) G V W V ρ g G ρ(g)(W ) W

ρ : G GL(V ) {0} V V ρ

G ρ : G GL(V ) G W

V

G W W V ρ| W ρ

G V 1 V 2 F f : V 1 V 2

ρ

ρ|

W

: G GL(W )

g

ρ(g)

G

ρ 1

:

G

GL(V 1 ) ρ 2

:

G GL(V 2 )

(f ) V 1 ρ 1 (f ) V 2 ρ 2

V

ρ : G GL(V ) G

W V

W

µ : G GL(V /W )

g µ(g)

µ(g)(v + W ) = ρ(g) + W, v V G V /W

ρ : G GL(V ) G

V

V ρ {0} V ρ

{0}

ρ V

=

1

n N n 2 F S n F n

ρ : S n GL(F n )

σ

ρ(σ)

W V

(v 1 ,

ρ(σ)(v 1 ,

,

v n ) F n

F n

, v n ) = (v σ 1 (1) ,

,

v σ 1 (n) ),

E

= {(v 1 ,

, v n ) F n : v 1 + ··· + v n = 0}

D = {(v,

, v) F n : v F}

ρ

G ρ : G GL(V ) G V v V \{0} W V

{ρ(g)(v) : g G}

= {0}

W = V V ρ

ρ

ρ W

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2 F f : V 1 V 2 ρ 1 ρ 2

f F V 1 = V 2 = V λ F f = λ · V

f (f )

V 1 ρ 1 ρ 1 (f ) = {0}

(f ) = V 1

= 0 (f ) = {0}

(f ) = V 2 f F f

λ F

f λ· V = 0

f = λ · V

f

det(f λ · V ) = 0

f λ · V

V 1 V 2 F V 1 V 2

V 1 V 2 = {(v 1 , v 2 ) : v 1 V 1 , v 2 V 2 },

V F W 1 W 2 V V W 1 W 2 V = W 1 W 2 W 1 + W 2 = V W 1 W 2 = {0} V W 1 W 2

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2 F ρ 1 ρ 2

ρ 1 ρ 2 : G GL(V 1 V 2 )

g

(ρ 1 (g), ρ 2 (g))

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2 G ρ 1 ρ 2 R 1 : G GL(n, F) R 2 : G GL(m, F) G ρ 1 ρ 2

R 1 R 2 : G

g

GL(n + m, F)

R 1 (g)

R 2 (g) = R 1 (g)

0

R 2 (g) .

0

V 1 V 2

, f m } V 1 V 2

V 1 V 2

F {e 1 ,

, e n } {f 1 ,

{e i f j : i ∈ {1,

, n}, j ∈ {1,

, m}}.

v = i=1 n λ i e i V 1 w = j=1 µ j f j V 2

m

v w =

n

m

i=1 j=1

λ i µ j e i f j V 1 V 2 .

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2

F {e 1 ,

ρ 1 ρ 2

V 1 V 2

,

e n } {f 1 ,

,

f m }

ρ 1 ρ 2 : G GL(V 1 V 2 )

g

ρ 1 (g) ρ 2 (g)

V F

V

V = F (V, F).

, e n }

V {e 1 ,

. , n

{φ 1 ,

, e n }

V F {e 1 ,

, φ n }

i

1,

.

.

φ i

: V

F

G G

j ∈ {1,

{φ 1 ,

, n} φ i (e j ) = δ ij

, φ n } V

V

V

V F f F (V ) f

f : V

V

φ

φ f

f F (V ) A f V f A

G ρ : G GL(V ) G V ρ G

ρ : G GL(V )

g

ρ g 1

V F W V W V W V

W 0 = {φ V : w W (φ(w) = 0)}.

W V

W 0 = {v V

: φ W (φ(v) = 0)}.

V V

V V

V

Z V W Z V F (V )

V V

F W

f

(W 0 ) 0 = W

(W 0 ) 0 = W

Z W

Z W W 0 Z 0

f (W ) W

f (W )

V /W 0 W V /W 0 W

W 0 Z 0

W

f (W 0 ) W 0 f (W 0 ) W 0

(W 0 ) = (V ) (W ) (W 0 ) = (V ) (W )

G ρ : G GL(V ) G V W V W V

W ρ W 0 ρ W ρ W 0 ρ

G ρ : G GL(V ) G V ρ ρ

n N F A M n (F) A

(A) =

n

i=1

A ii ,

A A

n N F A, B M n (F) (A + B) = (A) + (B) λ F (λA) = λ · (A) (AB) = (BA) B BAB 1 = (B)

A T = (A)

V F f F (V ) f (f ) f V

G ρ : G GL(V ) G V F G ρ

χ ρ : G F

g

(ρ(g))

G ρ : G GL(V ) G V

χ ρ (e) = (V ) = (ρ).

G G F 1 G 1 1

G χ G

g, h G

χ(ghg 1) = χ(h).

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2 F ρ 1 ρ 2 χ ρ 1 = χ ρ 2

G ρ 1 : G GL(V 1 ) ρ 2 : G GL(V 2 ) G V 1 V 2 F g G

χ ρ 1 ρ 2 (g)

=

χ ρ 1 (g) + χ ρ 2 (g)

χ ρ 1 ρ 2 (g) = χ ρ 1 (g) · χ ρ 2 (g)

n N n 2 F S n F n

ρ : S n GL(F n )

σ

ρ(σ)

,

ρ(σ)(v 1 , v n ) F n

,

v n ) = (v σ 1 (1) ,

,

v σ 1 (n) ),

(v 1 ,

σ S n χ ρ (σ) σ

V F ρ : G GL(V ) 1 G GL(V ) F χ ρ ρ G 1 G F

F m F ζ F ζ m = 1

m N F m m

f F (V )

f m

V

F

=

V

V

f m

G m N g G g m = e F m m ρ : G GL(V ) G F g G V ρ(g) m

G m N g G g m = e F m m χ G G F g G χ(g) m

F c : F F F c(ζ) = ζ 1 ζ

F

c(λ) = λ

F

G m N

g G g m = e F m m

GL(V ) G F

ρ(g)

g G V

ρ : G

 

ζ 1

0

0 ζ 2

0 0

···

···

···

0

0

ζ n

 

ρ g 1

ζ

1

1

0

0

ζ

···

2 ···

0

1

0

···

0

0

1

ζ

n

 

=

 

ζ 1

0

0

.

0

ζ 2

0

···

···

···


0

0

ζ n

 

,

ζ 1 ,

, ζ n m

χ ρ g 1 = χ(g).

g g 1 g

χ(g) = χ g 1 = χ(g) χ(g) F

F C V

V

F

·, · : V × V

F

λ, µ F

u, v, w

V

C C

λu + µv, w = λ u, w + µ v, w

u, λv + µw = λ u, v + µ u, w u, v = v, u

v, v = 0 v = 0

v,

v R

+

0

V C ·, · f F (V ) V u, v V

f (u), f (v) = u, v . V V

G ρ : G GL(V ) G C V ρ(g) g G

·, · V

·, · G : V × V F

u, v G =

1

|G|

gG

ρ(g)(u), ρ(g)(v) ,

u, v V V

h G

ρ(h)

·, · G u, v V

ρ(h)(u), ρ(h)(v) G =

=

=

1

|G|

1

|G|

1

|G|

gG

gG

kG

ρ(g)(ρ(h)(u)), ρ(g)(ρ(h)(v))

ρ(gh)(u), ρ(gh)(v)

ρ(k)(u), ρ(k)(v)

= u, v G

ρ(g)